Effect of plasma exchange on COVID-19 associated excess of von Willebrand factor and inflammation in critically ill patients - Seibert, Felix Sebastian; Blázquez Navarro, Arturo; Hölzer, Bodo; Doevelaar, Adrian A. N.; Nußhag, Christian; Merle, Uta; Morath, Christian; Zgoura, Panagiota; Dittmer, Rita; Schneppenheim, Sonja; Wilhelm, Jochen; Babel, Nina; et al. (Scientific reports, 2022)
Ubiquitous microthromboses in the pulmonary vasculature play a crucial role in the pathogenesis of COVID-19 associated acute respiratory distress syndrome (ARDS). Excess of Willebrand factor (vWf) with intravascular multimer formation was identified as a key driver of this finding. Plasma exchange (PLEX) might be a therapeutic option to restore the disbalance between vWf and ADAMTS13. We report the effects of PLEX on vWf, ADAMTS13, inflammatory cytokines and parameters of ventilation. We investigated 25 patients, who were on mechanical ventilation for COVID-19 pneumonia with ARDS at two German university hospitals. All patients received PLEX as an ultima ratio measure for refractory ARDS. VWf antigen (vWf:Ag), ADAMTS13 activity, a cytokine panel mirroring the inflammatory situation and clinical parameters were assessed before and after three to six PLEX therapies with fresh frozen plasma. Before the PLEX sequence there was an excessive release of vWf:Ag (425.4 ± 167.5%) and mildly reduced ADAMTS13 activity (49.7 ± 23.3%). After the PLEX series, there was a significant increase of ADAMTS13 activity to 62.4 ± 17.7% (p = 0.029) and a significant decrease of vWf:Ag to 336.1 ± 138.2% (p = 0.041) resulting in a 63% improvement of the ADAMT13/vWf:Ag ratio from 14.5 ± 10.0 to 23.7 ± 14.6, p = 0.024. Comparison of parameters before and after individual PLEX sessions (n = 35) revealed a mean reduction of vWf from 387.8 ± 165.1 to 213.2 ± 62.3% (p = 0.001) and an increase of ADAMTS13 activity from 60.4 ± 20.1 to 70.5 ± 14.0% (p = 0.001). Parallelly, monocyte chemotactic protein-1 and interleukin-18 decreased significantly (p = 0.034 each). Along the PLEX sequence lactate dehydrogenase (p = 0.001), C-reactive protein (p = 0.001), and positive end expiratory pressure (p = 0.01) significantly decreased accompanied by an improvement of Horovitz index (p = 0.001). PLEX restores the disbalance between ADAMTS13 and vWf:Ag, a driver of immunothrombosis. Moreover, it reduces the inflammatory state and is associated with a benefit of ventilation parameters. These findings render a further rationale to regard PLEX as a therapeutic option in severe COVID-19.
Gesehen am 28.06.2022